Learning from teacher educators: Reflecting on the certainty of teaching 'recipes' - Hall, Stephen J. * (MELTA, 2013)
Change towards an interactive classroom is often blocked by lack of acceptance of new techniques which require changes in a teachers’ role away from step-by-step sequences or `recipes’. Such ‘recipes’ while useful for novice teachers may not work in all contexts. This paper describes how culturally based perceptions of a teacher’s role impact on acceptance of classroom innovation and suggests teacher reflective practice. Building acceptance of differing methodologies in the early phases when first impressions count is therefore linked to reflection and lessons from in service teacher education. This paper uses rural in-service doctoral data and links research findings to classroom practice, focused on developing cross cultural acceptance of change. Techniques are suggested for bridging cultural gaps with reflective tools. These techniques drawn for research are presented by examining the roles we play as either teachers or teacher educators who wish to ‘cook up’ learning in interactive classrooms.